(untitled) (Research, Society and Development, 2021)
Goal: To outline the main health evaluation (HE) technologies used in health services in Brazil. Method: scoping review in databases, with papers published until July 18 2021. Papers with health evaluation and costs, results and economic indexes were included. All the papers with none of the aforementioned components and literature reviews, unavailable texts, legal opinions and decisions from governmental agencies and papers developed outside Brazil were excluded. Results: In the end, 10 papers were considered for this review. Discussion: The papers showed relevant data, although an improvement of the utilization of health economy concepts are needed for a better methodology in health evaluation. Health evaluation provide efficient evidences for decisions, improving resource deployment, offering safer and better health services, also enhancing health services accessibility. Conclusions: It is vital to include values such as HR appraisal, early return to work, cure, length of stay and costs of evaluated devices in the next health evaluations.